2017
DOI: 10.1038/s41598-017-14009-4
|View full text |Cite
|
Sign up to set email alerts
|

Non-linear effects and thermoelectric efficiency of quantum dot-based single-electron transistors

Abstract: By means of advanced numerical simulation, the thermoelectric properties of a Si-quantum dot-based single-electron transistor operating in sequential tunneling regime are investigated in terms of figure of merit, efficiency and power. By taking into account the phonon-induced collisional broadening of energy levels in the quantum dot, both heat and electrical currents are computed in a voltage range beyond the linear response. Using our homemade code consisting in a 3D Poisson-Schrödinger solver and the resolu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 68 publications
0
15
0
Order By: Relevance
“…Recently, Talbo et al [ 23 ] reported that in quantum dot‐based single‐electron transistors, the theoretically calculated ZT can go up to 200. Urban predicted that quantum dot hybrid arrays may lead to advanced TE performance and silicon‐based TE devices could have a prominent role in this possible future with a moderate ZT .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Talbo et al [ 23 ] reported that in quantum dot‐based single‐electron transistors, the theoretically calculated ZT can go up to 200. Urban predicted that quantum dot hybrid arrays may lead to advanced TE performance and silicon‐based TE devices could have a prominent role in this possible future with a moderate ZT .…”
Section: Introductionmentioning
confidence: 99%
“…For instance, in molecular junctions, the thermoelectric voltage and thermopower can distinguish between different transport mechanisms [7][8][9] . Thermopower in quantum dots was studied over two decades ago, both theoretically and experimentally [10][11][12] , with recent resurging interest focusing on role of interactions and non-linearity on thermoelectric efficiency [13][14][15][16][17][18][19][20][21][22] (see review in, e.g., Ref. 23).…”
Section: Introductionmentioning
confidence: 99%
“…The drag effect is a phenomenon, where a current flowing in a so-called drive conductor induces a voltage across a nearby drag conductor via the Coulomb interaction [16]. It has been shown by experimental and theoretical arguments that the cotunneling process is essential to obtain a correct qualitative understanding of the transport and drag properties in a Coulomb-coupled double quantum dot [17,18]. In addition, a dynamical signature of the Coulomb-blockade is seen, where the excited states are more active than the ground state even at a low electron number [19].…”
Section: Introductionmentioning
confidence: 99%